ANALISIS REGULASI DAN DAMPAK PEMBENTUKAN HOLDING BUMN SEKTOR PERBANKAN DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA - Intan Aprillia Maharani; Laela Meiliana Putri; Chyntia Marcella Putri (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Abstract. Indonesia’s national development goals, as mandated by the 1945 Constitution, focus on equal distribution of social welfare. In the economic context, State-Owned Enterprises (BUMN) have a strategic role as the main drivers of national economic development and growth. Changes in regulations related to BUMN, especially through Law Number 19 of 2003, open up opportunities for more strategic restructuring, including the formation of a Holding Company. BUMN holding aims to increase efficiency, competitiveness and company value through integrated management in key sectors such as banking, energy and infrastructure. This research analyzes the steps for establishing a holding in the banking sector, with PT Danareksa as the parent, involving eight government-owned financial entities, including Bank Mandiri, BRI and BNI. From a legal perspective, the formation of a holding company is faced with the challenge of complying with Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition. This study evaluates the legal and economic implications, and examines the extent to which the formation of a holding company can support equal distribution of welfare without violating the principles of fair business competition. The results of the research are expected to provide strategic recommendations for the government in developing an effective and legally based BUMN restructuring policy. Keywords: Banking Holding, BUMN, Business Competition Abstrak. Tujuan pembangunan nasional Indonesia, sebagaimana diamanatkan oleh UUD 1945, menitikberatkan pada pemerataan kesejahteraan masyarakat. Dalam konteks perekonomian, Badan Usaha Milik Negara (BUMN) memiliki peran strategis sebagai penggerak utama pembangunan dan pertumbuhan ekonomi nasional. Perubahan regulasi terkait BUMN, khususnya melalui UU Nomor 19 Tahun 2003, membuka peluang untuk restrukturisasi yang lebih strategis, termasuk pembentukan Holding Company. Holding BUMN bertujuan untuk meningkatkan efisiensi, daya saing, dan nilai perusahaan melalui pengelolaan terintegrasi di sektor-sektor utama seperti perbankan, energi, dan infrastruktur. Penelitian ini menganalisis langkah pembentukan holding di sektor perbankan, dengan PT Danareksa sebagai induk, yang melibatkan delapan entitas keuangan milik pemerintah, termasuk Bank Mandiri, BRI, dan BNI. Dari perspektif hukum, pembentukan holding dihadapkan pada tantangan kepatuhan terhadap UU Nomor 5 Tahun 1999 tentang Larangan Praktik Monopoli dan Persaingan Usaha Tidak Sehat. Studi ini mengevaluasi implikasi hukum dan ekonominya, serta mengkaji sejauh mana pembentukan holding dapat mendukung pemerataan kesejahteraan tanpa melanggar prinsip persaingan usaha yang sehat. Hasil penelitian diharapkan memberikan rekomendasi strategis bagi pemerintah dalam menyusun kebijakan restrukturisasi BUMN yang efektif dan berlandaskan hukum. Kata Kunci: Holding Perbankan, Persaingan Usaha